2014
DOI: 10.5606/kbbihtisas.2014.25986
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiofrequency thermal ablation method on nasal mucociliary activity in patients with inferior turbinate hypertrophy

Abstract: It was detected that RFTA has no adverse effect on mucociliary activity in the treatment of inferior turbinate hypertrophy, and this method is notably effective in relieving the nasal obstruction caused by inferior turbinate hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Uz et al and Parida et al used the SCT and VAS to evaluate the efficacy of RFTA and the postoperative morbidity associated with the procedure. 5 9 They reported no adverse effects of RFTA on mucociliary activity and a significant improvement in VAS scores. Duran and Ulkü obtained similar results with respect to MCC.…”
Section: Discussionmentioning
confidence: 94%
“…Uz et al and Parida et al used the SCT and VAS to evaluate the efficacy of RFTA and the postoperative morbidity associated with the procedure. 5 9 They reported no adverse effects of RFTA on mucociliary activity and a significant improvement in VAS scores. Duran and Ulkü obtained similar results with respect to MCC.…”
Section: Discussionmentioning
confidence: 94%
“…The in vivo nasal MCC can be measured with the SNTT. In literature, most of the authors reported no significant changes in SNTT before and after radiofrequency ablation of inferior turbinate 1,14,15 . Karatas et al, 16 comparing the effects of RFVTR using 2 magnitudes of energy, suggested that the energy value could influence the MCC.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, most of the authors reported no significant changes in SNTT before and after radiofrequency ablation of inferior turbinate. 1,14,15 Karatas et al, 16 comparing the effects of RFVTR using 2 magnitudes of energy, suggested that the energy value could influence the MCC. In that study, higher magnitudes of energy, elongating the healing process, also prolonged the SNTT.…”
Section: Discussionmentioning
confidence: 99%
“…[7,8] Tıkayıcı uyku apne sendromundaki tedavi yöntemlerinin burnun mukosiliyer aktivitesine etkisini araştıran çok sayıda çalışma vardır. [9][10][11][12][13][14] Ancak TUAS'ın burun hava yolunda klirense etkisi yeteri kadar incelenmemiştir. Gün içinde sakarin testinin değişimleri de net değildir.…”
Section: Discussionunclassified